Plant Cyclopeptides - Tan, Ning-Hua; Zhou, Jun (Chemical reviews, 2006)
The progress in the chemistry and biology of 455 cyclopeptides discovered from higher plants during 1959-2005 with 347 references is discussed. On the basis of their structural skeletons and distributions in plants, systematic structural classification of plant cyclopeptides which are divided into two classes, five subclasses, and eight types are proposed.